Colonization of breastfed infants by Bifidobacterium longum subsp. infantis EVC001 reduces virulence gene abundance. (August 2018) - Casaburi, Giorgio; Frese, Steven A.
Abstract: The infant gut microbiome is rapidly colonized by bacteria from the environment after birth, and this gut ecosystem can facilitate expansion of potential pathogens. Human milk shapes the infant gut microbiome and has evolved to foster the growth of specific bacteria. Breastfed infants fed the coevolved infant gut symbiont Bifidobacterium longum subsp . infantis EVC001 had significant modifications to their gut metagenome, including a decreased number of virulence factor genes.